Analysis of Trademark Cancellation Due to Elements of Imitation - Purwanto Setiawan (International Journal of Education, Vocational and Social Science, 2025)
This study analyzed the regulations regarding the protection of foreign famous brands in Indonesia and the implementation of these regulations. This study used a normative legal research design by describing the reality and then compared it with applicable regulations or existing legal theories to answer the problem. The case analyzed in this study is the brand dispute between J Casanova and Irawan Gunawan as the owner of the Casanova brand. From the results of the study it was found that until now there has been no definite definition of famous brand in Indonesia. This is exacerbated by the weak legal structure in Indonesia, which causes the legal process regarding cases related to the brand to not be fulfilled with justice, usefulness and legal certainty. As in this case, there is confusion in determining what can cause a brand to be called a famous brand, and what kind of case is referred to as a famous brand impersonation. Law enforcers appear to be still weak in deciding whether the brand to be registered has an element of equality in principle with respect to famous brand that have been previously registered or not.